Activation of protic, hydridic and apolar E−H bonds by a boryl‐substituted GeII cation - Mangan, R; Rit, A; Sindlinger, C; Tirfoin, R; Campos, J; Hicks, J; Christensen, K; Niu, H; Aldridge, S (Wiley, 2019)
The synthesis of a boryl‐substituted germanium(II) cation, [Ge{B(NDippCH)2}(IPrMe)]+, (Dipp=2,6‐diisopropylphenyl) featuring a supporting N‐heterocyclic carbene (NHC) donor, has been explored through chloride abstraction from the corresponding (boryl)(NHC)GeCl precursor. Crystallographic studies in the solid state and UV/Vis spectra in fluorobenzene solution show that this species dimerizes under such conditions to give [(IPrMe){(HCNDipp)2B}Ge=Ge{B(NDippCH)2}(IPrMe)]2+ (IPrMe = 1,3‐diisopropyl‐4,5‐dimethylimidazolin‐2‐ylidene), which can be viewed as an imidazolium‐functionalized digermene. The dimer is cleaved in the presence of donor solvents such as [D8]thf or [D5]pyridine, to give monomeric adducts of the type [Ge{B(NDippCH)2}(IPrMe)(L)]+. In the case of the thf adduct, the additional donor is shown to be sufficiently labile that it can act as a convenient in situ source of the monomeric complex [Ge{B(NDippCH)2}(IPrMe)]+ for oxidative bond‐activation chemistry. Thus, [Ge{B(NDippCH)2}(IPrMe)(thf)]+ reacts with silanes and dihydrogen, leading to the formation of GeIV products, whereas the cleavage of the N−H bond in ammonia ultimately yields products containing C−H and B−N bonds. The facile reactivity observed in E−H bond activation is in line with the very small calculated HOMO–LUMO gap (132 kJ mol−1).